Performance and safety of PowerPICC catheters and accessories: a prospective observational study - Troubil, Martin; Capozzoli, Giuseppe; Mussa, Baudolino; Hodne, Melinda; Hoerauf, Klaus; Alsbrooks, Kimberly (BMJ open, 2024)
OBJECTIVE: This study aimed to evaluate the safety and performance of PowerPICC catheters in a real-world setting. DESIGN: Prospective, observational, multicentre study. SETTING: Nine European countries, involving 14 centres. PARTICIPANTS: General patient population. INTERVENTION: PowerPICC catheter inserted by the clinician as standard of care with routinely collected outcomes followed through device removal or 180 days postinsertion. PRIMARY AND SECONDARY OUTCOMES MEASURES: Safety and performance outcomes were assessed for PowerPICC, PowerPICC SOLO 2 and PowerGroshong PICC. The primary safety endpoint was the incidence of symptomatic venous thrombosis (VT), and secondary safety endpoints included phlebitis, extravasation, vessel laceration, vessel perforation local infection, accidental dislodgment and catheter-related bloodstream infection (CRBSI). The primary performance endpoint was the percentage of patients whose PowerPICC device remained in place through the completion of therapy. The secondary performance endpoints included catheter patency, placement success in a single attempt and usability. RESULTS: The enrolled patients (N=451) received either PowerPICC, PowerPICC SOLO 2 or PowerGroshong PICC catheters. Across all devices, 1.6% of patients developed symptomatic VT, and CRBSI occurred in 1.6% of patients. There were no cases of phlebitis or extravasation and only three cases of vein laceration or vein perforation. The catheters showed high success rates in completing therapy (81.8%), maintaining patency (93.9%) and achieving successful placement in a single attempt (90.4%). Clinicians overwhelmingly agreed that both the guidewire and stylet (93.3% and 94.4%, respectively) were easy or very easy to use. CONCLUSIONS: This study demonstrates the safety and performance of PowerPICC catheters across diverse settings and patient cohorts in real-world hospital settings across Europe. The findings indicate that these catheters are safe and can be effectively used in the general patient setting and when inserted by a variety of clinicians. The low incidence of complications and high success rates further support the clinical utility of these catheters. TRIAL REGISTRATION NUMBER: NCT04263649.
Keywords: dospělí; Female; Europe; katétrové infekce; Catheterization, Peripheral; Adult; Venous Thrombosis; ženské pohlaví; Catheter-Related Infections; lidé; Evropa; zaváděcí katétry; Middle Aged; Catheters, Indwelling; prospektivní studie; Male; Prospective Studies; Aged; periferní katetrizace; Catheterization, Central Venous; katetrizace centrálních vén; lidé středního věku; senioři; mužské pohlaví; Central Venous Catheters; flebitida; žilní trombóza; centrální žilní katétry; Phlebitis; Humans